(untitled) (Bangladesh Journal of Medical Science, 2016)
Subcortical band heterotopia (SBH) is a disorder of neural migration. Also called as double cortex syndrome due to its appearance. Patient presents with mental retardation and epilepsy. Usually seizures start in first decade of life and may vary between focal seizures to generalized seizures. MRI is the diagnostic investigation of choice that reveals the characteristic findings. It is a rare disorder with only a few hundred cases reported till date. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.129-130